Memory effects in black phosphorus field effect transistors. (17th December 2021) - Grillo, Alessandro; Pelella, Aniello; Faella, Enver; Giubileo, Filippo; Sleziona, Stephan; Kharsah, Osamah; Schleberger, Marika; Di Bartolomeo, Antonio
Abstract: We report the fabrication and the electrical characterization of back-gated field effect transistors with a black phosphorus (BP) channel. We show that the hysteresis of the transfer characteristic, due to intrinsic defects, can be exploited to realize non-volatile memories. We demonstrate that gate voltage pulses allow to trap and store charge inside the defect states, which enable memory devices with endurance over 200 cycles and retention longer than 30 min. We show that the use of a protective poly(methyl methacrylate) layer, positioned on top of the BP channel, does not affect the electrical properties of the device but avoids the degradation caused by the exposure to air.